Interferensi Leksikal Bahasa Jawa ke dalam Bahasa Indonesia pada Karangan Siswa - Nindy Eka Putri; Mulyanto Widodo; Edi Suyanto (FKIP Universitas Lampung, 2017)
This research aimed to described forms interference lexical java language into indonesian language on students essay in the fifth grade students of SD Negeri Bukit Raya school year 2016/2017. Research method used in this research is descriptive of qualitative method. Data sources research on a students essay in the fifth grade students of SD Negeri Bukit Raya. Results of the research show that interference conducted by student includes interference in the basic from, affisx form, and reduplicated form. Based on the results on the research, was found thirty of interference conducted by students with nineteen basic forms, nine affix forms, and two reduplicated forms. Furthermore, the data is described in twenty primary meanings including lexical meanings, literal meanings, denotative meanings and ten secondary meanings covering grammatical, connotative, and figurative meanings.Penelitian ini bertujuan untuk mendeskripsikan bentuk-bentuk interferensi leksikal bahasa Jawa ke dalam bahasa Indonesia pada karangan siswa kelas V SD Negeri Bukit Raya tahun pelajaran 2016/2017. Metode penelitian yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Sumber data penelitian karangan siswa kelas V SD Negeri Bukit Raya. Hasil penelitian menunjukkan bahwa interferensi yang dilakukan siswa meliputi interferensi dalam bentuk dasar, bentuk berimbuhan, bentuk reduplikasi. Berdasarkan hasil penelitian yang telah dilakukan, ditemukan adanya tiga puluh interferensi yang dilakukan siswa dengan komposisi sembilan belas bentuk dasar, sembilan bentuk berimbuhan dan dua bentuk reduplikasi. Selanjutnya, data tersebut diuraikan ke dalam makna primer berjumlah dua puluh meliputi makna leksikal, makna literal, makna denotatif dan makna sekunder berjumlah sepuluh meliputi makna gramatikal, konotatif, dan makna figuratif.Kata kunci: interferensi leksikal, bahasa jawa, karangan siswa.